Case report: Adult-onset limb girdle muscular dystrophy in sibling pair due to novel homozygous LAMA2 missense variant - Katz, Matthew; Waddell, Leigh B.; Yuen, Michaela; Bryen, Samantha J.; Oates, Emily; Garton, Fleur C.; Robertson, Thomas; Henderson, Robert David; Cooper, Sandra T.; McCombe, Pamela A. (Frontiers in Neurology, 2023)
Recessive pathogenic variants in the laminin subunit alpha 2 (LAMA2) gene cause a spectrum of disease ranging from severe congenital muscular dystrophy to later-onset limb girdle muscular dystrophy (LGMDR23). The phenotype of LGMDR23 is characterized by slowly progressive proximal limb weakness, contractures, raised creatine kinase, and sometimes distinctive cerebral white matter changes and/or epilepsy. We present two siblings, born to consanguineous parents, who developed adult-onset LGMDR23 associated with typical cerebral white matter changes and who both later developed dementia. The male proband also had epilepsy and upper motor neuron signs when he presented at age 72. Merosin immunohistochemistry and Western blot on muscle biopsies taken from both subjects was normal. Whole exome sequencing revealed a previously unreported homozygous missense variant in LAMA2 [Chr6(GRCh38):g.129297734G>A; NM_000426.3:c.2906G>A; p.(Cys969Tyr)] in the proband. The same homozygous LAMA2 variant was confirmed by Sanger sequencing in the proband's affected sister. These findings expand the genotypic and phenotypic spectrum of LGMDR23.